A Systematic Review on the Antihyperglycemic Property and Effect of Roselle (Hibiscus sabdariffa Linn.) Fruit Peel Extract in Diabetic Male Rats (Rattus norvegicus) Induced by Streptozotocin - Aison, Marycel; Surisantos, Joshua Alvin; Chua, Erin Anjella; Kabiling, Ma. Danielle; Manalo, Kashima Mira; Maravilla, Edzyrel Ann; Natividad, Aldren Enrick; Medrano, Winny Kyla Therese; Cano, Earl Adriane A (Asian Journal of Biological and Life Sciences)
Aim/Background: Diabetes mellitus is a chronic disease that inhibits insulin production, which affects blood levels. Over-the-counter drugs regulate blood levels, while medicinal plants such as Roselle (Hibiscus sabdariffa Linn.) are used as a remedy. This systematic review aims to establish the antihyperglycemic properties of Roselle fruit peel extract, determine its effectiveness in diabetic male rats (Rattus norvegicus) induced by Streptozotocin, and evaluate the efficiency of Roselle fruit peel extract compared to over-the-counter diabetes medication; A comprehensive and systematic search of (1) Antihyperglycemic property and effect of Hibiscus sabdariffa Linn., (2) Samples used are diabetic male rats (3) Orally induced Streptozotocin given by medical professionals. Materials and Methods: The data were gathered through different databases, such as PubMed Central, the IOSR Journal of Pharmacy, EBSCOHost, Google Scholar, and ResearchGate; out of 100 studies retrieved, only 13 were utilized due to the elimination of the 87 by exclusion criteria. Diabetes is ranked 6th as the highest cause of death in the Philippines, ranking 9th worldwide. Results and Conclusion: In lieu of this, herbal or more organic forms of remedy are pursued by people who have diabetes. The review of studies shows that the Hibiscus sabdariffa Linn. plant possesses hypoglycemic, hyperlipidemic, and antioxidative properties due to the phytochemicals present. This review also solidifies the notion that Roselle extract and over-the-counter drugs have the same effect on blood sugar levels upon rat experimentation.